Kedehenat wada lemat : ewqaten latewled mastalalaf , be Foram for soshal stadis yaweyeyet madrak lay yaqarabu sehufoc - Shiferaw Baqala (Addis Ababa : Forum Social Studies, 2006)
The theme of this particular publication is : "From poverty to development", and is a collection of various discussion papers presented by various authors.
Includes bibliographical references.
In Amharic.
Keywords: Ethiopia -- Economic development; Ethiopia -- Economic conditions